Analisis Penerapan Generic Strategies pada Perusahaan (Studi Kasus pada PT Madubaru) - Kartika Pradana Suryatimur; Nibras Anny Khabibah; Axel Giovanni (Global Financial Accounting Journal, 2020)
This study aims to analyze the implementation of generic strategies implemented by the company. The strategy adopted by the company affects the company's position in competition. The research method used is descriptive qualitative case studies. This study uses investment data from PT Madubaru during 2008 - 2017. The data used are primary and secondary data. Primary data includes the results of interviews, and secondary data includes audited company financial reports. The results of this study indicate that companies cannot reduce production costs by simply improving technology to gain a competitive advantage through cost leadership. The company's failure to reduce production costs was due to the lack of availability of easy and cheap raw materials. Achieve a competitive advantage through cost leadership must meet the requirements, namely; minimizing costs, cheap raw materials, and utilizing appropriate technology.